Identifying the determinants of non-injection of covid-19 vaccine: A qualitative study in Urmia, Iran - Yoosefi Lebni, Javad; Irandoost, Seyed Fahim; Sedighi, Sardar; Ahmadi, Sina; Hosseini, Rana (Frontiers in Public Health, 2022)
Objective Extensive vaccination coverage is one of the most effective ways to control COVID-19 vaccine, but the tendency to inject the vaccine is always hampered and there are various determinants of non-injection. Hence, the present study was done with the aim of identifying the determinants of non-injection of COVID-19 vaccine with a qualitative approach in the city of Urmia in Iran. Methods The present study was conducted with a qualitative approach and conventional content analysis method among 36 people who refused to be vaccinated. Access to participants and data collection was done in person (28 interviews) and online (8 interviews) through targeted sampling and snowball method and semi-structured interviews. Data management was performed using MAXQDA-2018 software and its analysis was performed by Graneheim and Lundman method. Also, Guba and Lincoln criteria were observed to improve the quality of results. Results After analyzing the data, 3 main categories and 11 subcategories were obtained including (1) Individual factors (fear of short-term side effects of vaccine, personality traits, distrust of vaccines and pharmaceutical companies), (2) Socio-cultural factors (conspiracy theory, social learning, misconceptions about COVID-19, fatalism), legal and managerial factors (incomplete information, difficult and irregular access to vaccination centers, lack of restrictions and compulsion to be vaccinated, lack of incentives to be vaccinated). Conclusion The results showed that various determinants were involved in the non-injection of COVID-19 vaccine. Therefore, efforts to increase vaccination coverage require comprehensive measures at different levels and cross-sectoral cooperation between governmental and non-governmental institutions and organizations.